Software para estimativa da eficiência energética na produção de suínos - ASSIS, Claudemir C (2017)
Brazilian pig farming is an important farming activity, because besides it offering food of high nutritional value to the human population, it contributes for generation of employ and income in the country. Due to the need of produce food with environmental responsibility, the swine producers have adopted waste treatment practices on their property. Each time more, it is necessary that the producer know the degree of efficiency and sustainability of the production system utilized. In this sense, the energy balance has been used as a tool indicative of the rational use of resources. However, many producers still do not estimate the energy flow because they encounter difficulties in the energy conversions and other required calculations. Therefore, the present work presents the software ENERGYSWINE developed to help technicians and producers to determine the energy efficiency in swine production systems. The ENERGYSWINE program was developed in Microsoft's integrated development environment (IDE) for software development (Visual Studio) using the C# (C Sharp), HTML5, CSS3 and JavaScript languages. For the storage of the information of the system such as user, farm, data analysis and energy balance calculation, the SQLServer database was used. From a literature review, the specific energy coefficients for each input and output component were established. The energy balance calculation by ENERGYSWINE considers the ratio between all energy produced in the system and all energy consumed. When accessing the initial screen of the program, the user must fill out the form containing 22 questions. After all fields were answered, the software calculates the energy balance of the farm, and the user can view and print the report with the summary of energy balances already done. ENERGYSWINE software has demonstrated to be a suitable tool to calculate of manner quick and easy the energy balance of swine production systems. As future perspectives, new works can be developed to incorporate new modules and reports into updated versions of the program.